Kilka uwag o znaczeniu partytywnym dopełniacza w dokumentach kancelaryjnych XVI wieku - Zofia Szwed (Studia Rossica Posnaniensia)
The article deals with the way in which partitive meaning was expressed in genitive constructions in the 16th-century Russian language. It focuses on the problem of codependence between partitive meaning and the genitive inflection -u, correlation between the inflections -a/-u, and the semantics of nouns which took the inflection -u in the 16th-century administrative files.